2020
DOI: 10.1002/jbmr.4259
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Zoledronic Acid in Maintaining Areal and Volumetric Bone Density After Combined Denosumab and Teriparatide Administration: DATA-HD Study Extension

Abstract: Combined teriparatide and denosumab rapidly and substantially increases bone mineral density (BMD) at all anatomic sites. Discontinuation of denosumab however, results in high‐turnover bone loss and increased fracture risk. The optimal way to prevent this bone loss remains undefined. This study is a preplanned extension of the DATA‐HD study, where postmenopausal women with osteoporosis were randomized to receive 9 months of either 20 μg or 40 μg of teriparatide daily overlapping with denosumab (60 mg administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
1
16
1
Order By: Relevance
“…Similar changes were found in the DATA-HD Extension Trial by Ramchand and colleagues, where bone microarchitecture was evaluated 12 and 27 months after ZOL. (19,20) Aging is associated with a thinning of the cortex, leaving cortical remnants that resembles trabecular bone, and Zebaze and colleagues found that when including these as trabecular bone, trabecular density is overestimated. (28) Furthermore, there was a threefold underestimation of the increase in cortical porosity, when the compact cortical bone was evaluated without the trabecularized cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar changes were found in the DATA-HD Extension Trial by Ramchand and colleagues, where bone microarchitecture was evaluated 12 and 27 months after ZOL. (19,20) Aging is associated with a thinning of the cortex, leaving cortical remnants that resembles trabecular bone, and Zebaze and colleagues found that when including these as trabecular bone, trabecular density is overestimated. (28) Furthermore, there was a threefold underestimation of the increase in cortical porosity, when the compact cortical bone was evaluated without the trabecularized cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In the DATA-HD Extension Trial, postmenopausal women (n = 53) were treated with a combination of teriparatide and DMAB for 9 months followed by 6 months of DMAB therapy before receiving a single infusion of ZOL 5.5 to 8 months after the last DMAB. (19,20) Twelve months after ZOL, BMD was maintained at all sites; however, 27 months after ZOL, LS BMD had decreased (−3.7%) and BTMs increased toward baseline levels. The AfterDmab, a randomized clinical trial, allocated 57 postmenopausal women treated with DMAB for 2.0 to 2.4 years to either two injections of DMAB or a single infusion of ZOL.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, HORIZON study [21] had indicated that compared to risedronate, ZOL could more significantly improve BMD at lumbar spine (4.06% vs 2.71%), total hip (1.65% vs 0.45%), and femoral neck (1.45% vs 0.39%). Moreover, ZOL had a longer half-life time in bone, which could continuously reduce bone loss [22][23][24][25]. Treatment with annual infusion of ZOL was convenient and conducive to improve the compliance and persistence of osteoporosis patients and could still play a role for a long time after discontinuation [26].…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that participants reporting vigorous physical activity had on average 28.2 mg/cm 2 higher aBMD in the left total hip compared with inactive participants, after adjusting for multiple confounders, which corresponds to roughly 3% of the sample mean. To put this into context, a recent randomized clinical trial showed a 5.1% increase in total hip BMD after 15 months of pharmaceutical treatment [ 34 ]. However, encouraging inactive individuals to become vigorously physically active is challenging, and physical activity is likely not the sole solution to improving or maintaining BMD in the population.…”
Section: Discussionmentioning
confidence: 99%